Pengaruh E-Leadership Berbasis Siklus PDCA terhadap Kinerja Guru dan Pencapaian Target Menghafal 1 Juz Al-Qur'an - Dikdik, Asep; Komariah, Aan; Suryana, Asep; Suharto, Nugraha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Qur'anic education faces various challenges in adapting to digital transformation while maintaining the quality of education and Islamic values. This study examines the effect of e-leadership based on the Plan-Do-Check-Act (PDCA) cycle on teacher performance and students' 1 Juz Al-Qur'an memorization achievement target. This study used an explanatory quantitative approach. The research subjects were 16 teaching teachers, and the data collection method used was the descriptive choreographic survey method. Then, data analysis techniques such as normality, linearity, correlation, and determination coefficient tests will be used. This study found that e-leadership based on the PDCA cycle significantly improves teacher performance, as indicated by the coefficient of determination R² of 77.3%. This finding indicates that implementing e-leadership based on the PDCA cycle can explain most of the variability in teacher performance, especially in lesson planning, task execution, evaluation of results, and corrective actions. In addition, the results show that e-leadership also correlates reasonably strongly with achieving the 1 Juz Al-Qur'an memorization target, with an R² value of 44.6%. Although its contribution to memorization achievement is lower than its impact on teacher performance, the implementation of e-leadership based on the PDCA cycle still supports strategies for planning, implementing, monitoring, and evaluating student memorization. This finding confirms the principal's role in improving teacher performance. It encourages further research to identify other factors that can influence the success of e-leadership in the context of Islamic education.